ChemInform Abstract: Direct Amidation of N‐Boc‐ and N‐Cbz‐Protected Amines via Rhodium‐Catalyzed Coupling of Arylboroxines and Carbamates. Issue 18 (April 2016) - Lim, Diane S. W.; Lew, Tedrick T. S.; Zhang, Yugen
Abstract: A novel and direct route for converting N‐Boc‐ and N‐Cbz‐protected amines to amides is developed that is tolerant to a variety of acid‐sensitive and reducible functional groups.